The injector of high power electron linac for industrial application - Ayzatsky, M.I.; Biller, E.Z.; Dovbnya, A.N.; Khodak, I.V.; Kushnir, V.A.; Mitrochenko, V.V.; Stepin, D.L.; Zhiglo, V.F. (Вопросы атомной науки и техники, 2004)
In the paper the results of the experimental study on forming the electron bunches in the injector of a high current S- band linac are presented. The injector consists of a low voltage electron gun, bunching cavity and accelerating cavity. The influence of different factors on the beam spatial and energy characteristics is analyzed.